2014
DOI: 10.1248/bpb.b14-00177
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of <i>N</i>-Methyl-D-aspartate Receptor Subunits and c-Fos Expressing Genes in PC12D Cells by Nobiletin

Abstract: The N-methyl-D-aspartate (NMDA) receptor plays a key role in learning and memory. Our recent studies have shown that nobiletin from citrus peels activates the cAMP response element-binding protein (CREB) signaling pathway and ameliorates NMDA receptor antagonist-induced learning impairment by activating extracellular signal-regulated kinase. For the first time, we have shown that nobiletin significantly upregulated mRNA expression of the NMDA receptor subunits NR1, NR2A, and NR2B in PC12D cells. Furthermore, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These earlier studies demonstrated that nobiletin induces the activation of the protein A (PKA)/extracellular signal-regulated kinase (ERK)/ cAMP response element (CRE)-binding protein (CREB) intracellular signaling pathway, and subsequently up-regulates CRE-dependent transcription. 16,23) These findings were observed in subclone PC12D of the rat pheochromocytoma cell line PC12. Furthermore, nobiletin elevates the expression of memory-and transcription-related genes in PC12 and PC12D cells.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…These earlier studies demonstrated that nobiletin induces the activation of the protein A (PKA)/extracellular signal-regulated kinase (ERK)/ cAMP response element (CRE)-binding protein (CREB) intracellular signaling pathway, and subsequently up-regulates CRE-dependent transcription. 16,23) These findings were observed in subclone PC12D of the rat pheochromocytoma cell line PC12. Furthermore, nobiletin elevates the expression of memory-and transcription-related genes in PC12 and PC12D cells.…”
mentioning
confidence: 72%
“…In this study, whether nobiletin directly up-regulates neprilysin gene expression remains unclear. Previously, we showed that nobiletin evokes PKA/ERK/CREB signaling 23) and CRE-dependent transcription, 16) thus increasing the gene expression of the CREB-binding protein (CBP), 25) c-Fos, 24) c-jun, and Fra1 (data not shown) in PC12 and PC12D cells. In recent years, a number of studies have implicated epigenetic modifications in the expression of neprilysin.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, studies addressing the effects of specific flavonoid subgroups, including flavanols, anthocyanins, flavanones, and flavones, have shown that these constituents display potential to act as cognition-enhancing and neuroprotective agents (Vauzour et al, 2008 ; Kehr et al, 2012 ; Rendeiro et al, 2013 , 2014 ; Vauzour, 2014 ), to prevent many forms of cerebrovascular disease, or to function as anti-anxiety drugs (Hasenöhrl et al, 1998 ; Spencer, 2008 ; Zhang et al, 2012 ). Although studies ex vivo, in vivo , and in vitro have provided evidence supporting the effects of flavonoids on the central nervous system, the cellular, and molecular pathways through which these compounds modulate memory formation are not completely elucidated (Youdim et al, 2004 ; Nakajima et al, 2007 ; Spencer, 2007 ; Williams et al, 2008 ; Ballesteros et al, 2014 ; Kimura et al, 2014 ; Rendeiro et al, 2014 ). However, several studies have established that the hippocampus, which plays a central role as a substrate of fear memory and anxiety (Fendt and Fanselow, 1999 ; Sanders et al, 2003 ) and which is a component of the Behavioral Inhibition System (McNaughton and Gray, 2000 ), appears to be a target for the mnemonic effects of flavonoid metabolites (Bannerman et al, 2004 ; Wang et al, 2006 , 2009 ; Williams et al, 2008 ; Rendeiro et al, 2012 , 2014 ; Oliveira et al, 2013 ; Vauzour, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on its potent physiological activities, nobiletin has become an attractive candidate for use as a therapeutic agent. The physiological activities of nobiletin have been attributed to its ability to modulate cell-signaling pathways, including cAMP response elements (Nagase et al, 2005) and NF-B (Cui et al, 2010), as well as its ability to alter the expression of specific genes (Nemoto et al, 2013;Kimura et al, 2014). However, the molecular mechanisms of nobiletin are not clear because the target receptor molecules to which this compound might bind have not yet been definitively identified.…”
Section: Introductionmentioning
confidence: 99%